Nestedness of benthic diatom metacommunity in relation to species niche width and environmental variables in a large near-natural catchment - Qi, Xinxin; Liu, Guohao; Chen, Chuanwu; Wang, Yixia; Wang, Yaochun; Lin, Zongwei; Wu, Naicheng (Frontiers in Ecology and Evolution, 2024)
Insight into the non-random distribution patterns of species in different regions is a foundational aim of research in community ecology and biogeography. The nestedness pattern, which investigates changes in species composition and abundance, has been widely used in numerous studies. However, studies on the nestedness of benthic diatoms are extremely rare, and consequently little has been mentioned of their assemblage mechanisms. To fill this gap, based on 168 benthic diatom species from 147 sampling sites in the Thousand Island Lake (TIL) catchment, we calculated their nestedness and niche width with the aim of i) analyzing the nestedness of benthic diatoms communities with different attachment abilities in TIL; ii) calculating niche width differences between nested and idiosyncratic species with different attachment abilities; iii) investigating the differences in alpha and beta diversity between nested and idiosyncratic sites; iv) examining whether environmental variables influencing the nestedness of benthic diatom communities are dependent on attachment ability. The results demonstrated a significant nestedness pattern in the benthic diatom metacommunity, and the sampling sites of low attachment species not only exhibited a nestedness pattern, but also with a lower nestedness value compared to the sampling sites of all species. Nested and idiosyncratic species differed in niche width, whereas differences between nested and idiosyncratic species of low attachment species were smaller. Additionally, significant differences in alpha and beta diversity were observed between nested and idiosyncratic sites. Furthermore, it was revealed that the nestedness of benthic diatom metacommunity in our study area were mostly influenced by local environmental variables. Our study contributes to the understanding of the significant nestedness observed in benthic diatom metacommunity in TIL, highlighting its relevance to biodiversity conservation efforts.